Recognising and Treating Complicated Fissuring Perianal Crohn Disease: A South-East Scotland Cohort Study. Issue 1 (12th January 2022) - Burgess, Christopher J.; Clark, Claire; Khedim, Cher-Antonia; Armstrong, Katherine; Henderson, Paul; Wilson, David C.
Abstract : ABSTRACT: Fissuring perianal Crohn disease (CD) is not recognised as a perianal phenotype in Montreal/Paris inflammatory bowel disease classifications; however, can occasionally present as complicated disease with severe perianal pain driving increasingly intensive medical therapy despite well controlled luminal disease. We identified a regional cohort of prospectively acquired incident cases of paediatric CD diagnosed <16 years of age in South-East Scotland over a 19-year period (1999–2018), and conducted a retrospective review of complicated fissuring perianal CD causing severe pain related to anal sphincter complex spasm at defecation. Two hundred forty-seven new cases of paediatric CD were diagnosed with complicated fissuring perianal disease identified in 4 described cases (cumulative incidence 1.6%). These patients with marked fissuring and refractory anal sphincter complex spasm required neurostimulation-guided, 4-quadrant, anal intrasphincteric botulinum toxin (BT). All experienced immediate success, measured by cessation of spasms, with variable ongoing symptom relief after median (range) 3 (2–5) BT injections.